2022
DOI: 10.3389/fpls.2021.789065
|View full text |Cite|
|
Sign up to set email alerts
|

Defeating Huanglongbing Pathogen Candidatus Liberibacter asiaticus With Indigenous Citrus Endophyte Bacillus subtilis L1-21

Abstract: Huanglongbing (HLB) has turned into a devastating botanical pandemic of citrus crops, caused by Candidatus Liberibacter asiaticus (CLas). However, until now the disease has remained incurable with very limited control strategies available. Restoration of the affected microbiomes in the diseased host through the introduction of an indigenous endophyte Bacillus subtilis L1-21 isolated from healthy citrus may provide an innovative approach for disease management. A novel half-leaf method was developed in vitro to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 62 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…In this study, using GFP‐tagged endophyte L1‐21, we also found that colonization in the midgut of psyllids made it possible to reduce pathogen concentration in psyllids, but the colonization of this bacterium was not found in the eggs, as C Las could not be found in the eggs 26 . Efficient colonization and time of endophyte B. subtilis L1‐21 in citrus plants played a significant role in C Las reduction, 30 as proposed for the psyllid in the present study. The mechanisms of dual antagonism employed by endophyte L1‐21 inside citrus psyllid require further study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In this study, using GFP‐tagged endophyte L1‐21, we also found that colonization in the midgut of psyllids made it possible to reduce pathogen concentration in psyllids, but the colonization of this bacterium was not found in the eggs, as C Las could not be found in the eggs 26 . Efficient colonization and time of endophyte B. subtilis L1‐21 in citrus plants played a significant role in C Las reduction, 30 as proposed for the psyllid in the present study. The mechanisms of dual antagonism employed by endophyte L1‐21 inside citrus psyllid require further study.…”
Section: Discussionmentioning
confidence: 66%
“…Recently, our study for more than 6 years suggested that C Las was successfully eliminated from diseased citrus hosts using a large‐scale endophyte‐mediated disease control strategy. The endophyte B. subtilis L1‐21 helps mitigate the pathogen by more than 90%, where diseased citrus plants show robust growth 30 . Following the interesting strategy of using endophytes in HLB‐affected citrus groves, the source ACP, responsible for carrying C Las from the diseased host, must be carefully checked to stop the spread of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…These microbes not only produce volatile compounds that enhance the fruit's flavor but also enhance its ability to defend against pests and pathogens (Daranas et al, 2019). Bacillus stimulates plant growth, and recent research has found that Bacillus subtilis in citrus trees can effectively resist the Huanglongbing pathogen (Daivasikamani, 2009;Yu et al, 2011;Munir et al, 2022). In strawberry and apples, lactic acid bacteria can be used as a biological control agent for disease (Trias et al, 2009;Tsuda et al, 2013;Zhou et al, 2017).…”
Section: The Relationship Between Vocs and The Bacterial Microbiotamentioning
confidence: 99%
“…In traditional crop breeding, breeders typically pay limited attention to the plant microbiome or PSMmicrobiome interactions based on crop yield and other traits. In recent years, phyllosphere microorganisms have been found to regulate host stress resistance, and they are involved with VOC emissions (Matsumoto et al, 2021;Munir et al, 2022). Phyllosphere pathogenic microorganisms can alter plant VOC emissions by inducing plant defense responses or disrupting normal metabolism (Matsumoto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Liberibacter spp. (Blaustein et al, 2018; Munir et al, 2022; Trivedi et al, 2016; Zhang et al, 2021). However, empirical evidence supporting this idea is lacking.…”
Section: Introductionmentioning
confidence: 99%